EFEKTIVITAS DAN EFISIENSI JEMBATAN RANGKA KAYU SEBAGAI ALTERNATIF RANGKA JEMBATAN PEJALAN KAKI - Nurjanah Nurjanah; Hazairin Nikmatul Lukma (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract In remote areas, there are many simple bridges (non-engineered bridges) that are damaged. One alternative to solve the problem of bridges in remote areas for pedestrians is to use a wooden frame bridge. The truss system bridge is an ideal form and is easily renewable and easily available which is prone to buckling. Some forms of truss bridges that are widely applied are the Warren truss, Pratt truss, Howe truss, and K-truss types. This study discusses the effect of frame shape on the ratio of weight and deflection that occurs due to pedestrian loads on short spans (L=4m). In the development of this frame shape, it refers to the frame shape that is widely applied, using loading according to SNI 1725-2016 and cold rolled cross section analysis based on SNI 7971-2013. The data required is the height of the girder is 2.1m and the width is 0.7m. Refers to SNI 1725 Loading bridges, and the control structure refers to SNI T-12-2004 (Concrete Structure Planning for Bridges). The analysis begins by determining the dimensions of the girder geometry, Sap 2000 software. The results of the analysis show that the calculation with Sap 2000 and graphed shows the equation y = 82.782 x δ – 2.555562, the maximum deflection is L/500, which is 0.08 cm. So, the load that produces a deflection of 0.08 cm is 7.425 kg. In this plan, the katu sengon material is used with a beam dimension of 8/12 and in the final design the bending stress is 32 kg/cm2 which is smaller than the allowable bending stress of 100 kg/cm2 Keywords: Truss Bridge, Wooden, Pedestrian Bridge, SAP 2000